Fenomena Bermain Generasi Z dan Hubungannya dengan Eksistensi Ruang Bermain Terbuka di Lingkungan Perumahan Sederhana - John Fredy Bobby Saragih (Bina Nusantara University, 2012)
Play is something important for children development. In fact, there are many children who can not play as they should. Even playgrounds provided tend not to be able to function optimally. Even there is a tendency of provided playgounds abandoned by children. One example is the generation Z, highly technologyliterate children or called net generation. They would rather to interact with computers and communicate with the online system than meeting their friends. It seems to the generation Z that space is not limited by physical things, because they can create their spaces in the virtual status. Noting this indication, the existence of parks and playgorunds provided for public (including children) to do any activities, is likely to be reviewed. The low level of children visit illustrates that parks/playgrounds do not much interest them.